Certain investigations on multi input â€“SEPIC-RE boost-system with enhanced-response - Jagadish Kumar, B.; Basavaraja Banakara, Dr. (International Journal of Engineering and Technology, 2018)
Recent developments in converters have given pathway to high-gain-step up converter having low output voltage ripple. High-gain-step up converters can be found between Photovoltaic Voltage (PV) and Direct-Current (D-C) loads. The intention of this work is to identify multi converter system for multiple input sources and to improve time response of high-gain-step up-converter. Closed-loop Multi-Converter System (MCS) is utilized to regulate load voltage. This effort recommends suitable-controller for â€œclosed-loop-controlled-SEPIC-REBOOST Converter fed DC motorâ€. The estimation of the yield in â€˜open-loopâ€™&â€˜closed- loop-circuitâ€™ has been done using MATLAB or Simulink. Closed-loop-control of MCS with PI and FOPID-Controllers are investigated and their responses are evaluated in conditions of rise time, peak time, settling time and steady state error. It is seen that FOPID controlled MCS gives better time domain response in terms of motor speed. A â€˜Prototype of MCSâ€™ has been fabricated in the laboratory& the â€˜experimental-resultsâ€™ are authenticated with the simulation-results.Â Â Â